2014
DOI: 10.3906/biy-1310-17
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive evaluation of phytoestrogen accumulation in plants and in vitro cultures of Medicago sativa L. ‘Elçi’ and natural tetraploid Trifolium pratense L.

Abstract: IntroductionHigher plants synthesize a wide variety of phenolic compounds during their regular growth and development. These phenolic compounds are products of the phenylpropanoid biosynthetic pathway and generally accumulate at relatively high concentrations in cell vacuoles, and they are usually chemically associated with sugars (Coronado et al., 1995). Flavonoids are found throughout the plant kingdom, whereas isoflavones are more restricted and particularly prevalent in the subfamily Papilionoideae of Faba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…In this study, concentrations of formononetin were in ranges of 0.22–4.68 mg/g, 0–0.95 mg/g and 0.10–1.54 mg/g in leaves, flowers and stems, respectively, while these values for biochanin A were 0.59–5.94 mg/g, 0.17–1.52 mg/g and 0.08–0.56 mg/g ( Table 2 ). These ranges correspond with several published results [ 5 , 23 , 32 , 33 , 36 , 37 ]. Still, higher values are also observed and can go up to 28.5 mg/g for formononetin [ 38 ] and 17.9 mg/g for biochanin A [ 7 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, concentrations of formononetin were in ranges of 0.22–4.68 mg/g, 0–0.95 mg/g and 0.10–1.54 mg/g in leaves, flowers and stems, respectively, while these values for biochanin A were 0.59–5.94 mg/g, 0.17–1.52 mg/g and 0.08–0.56 mg/g ( Table 2 ). These ranges correspond with several published results [ 5 , 23 , 32 , 33 , 36 , 37 ]. Still, higher values are also observed and can go up to 28.5 mg/g for formononetin [ 38 ] and 17.9 mg/g for biochanin A [ 7 ].…”
Section: Discussionsupporting
confidence: 92%
“…The content of these compounds varies greatly depending on different factors. However, the majority of studies found that formononetin and biochanin A are the dominant isoflavones in red clover [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. In this study, concentrations of formononetin were in ranges of 0.22–4.68 mg/g, 0–0.95 mg/g and 0.10–1.54 mg/g in leaves, flowers and stems, respectively, while these values for biochanin A were 0.59–5.94 mg/g, 0.17–1.52 mg/g and 0.08–0.56 mg/g ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e natural tetraploid T. pratense L. (red clover) chromosome number is 2n = 4x = 28 (Buyukkartal & Colgecen, 2007). e natural tetraploid T. pratense L. variety contains more secondary metabolites than the diploid variety of the plant (Çölgeçen et al, 2014;Khaosaad et al, 2008). Its phytoestrogenic activity is very high mostly due to its content of isoflavones, which can act as estrogen agonists or antagonists, depending on the compound and its content in the body (Dog, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Medicago is also known as a model plant because of its ability to regenerate in vitro in plant tissue culture (Erişen, 2006). M. sativa is also reported to reduce the menopausal symptoms in women by increasing the levels of estrogen (Gülen, 2013;Çölgeçen et al, 2014;Franciscis et al, 2019). M. sativa is rich in flavonoids, too.…”
Section: Introductionmentioning
confidence: 99%